A low-cost uncooled infrared aluminum microbolometer in a standard CMOS technology. (September 2014) - Shen, Ning; Tang, Zhen'an; Feng, Chong
This article introduces the implementation of a low-cost 4 × 5 pixel array uncooled infrared microbolometer together with its integrated readout circuit in a standard 0.5-µm CMOS technology and post-CMOS process. Each pixel, which has a size of 80 µm × 80 µm, is a novel structure of aluminum microbolometer fabricated by etching the surface sacrificial layer without any additional masking and lithography procedure. The aluminum microbolometer consists of an aluminum thermistor and a thermally isolated micromachined membrane suspended by two arms. The thermal conductance, thermal time constant, thermal capacitance, and responsivity of the aluminum microbolometer are experimentally measured.